Ethical dilemmas in "dying well": When the subjective times do not accompany the chronological times of the disease - Cabrera, Maria Emilia (2022)
Throughout this text, we will analyze the concept of time and how this time could determine or limit what we understand in palliative care as "dying well". To understand these concepts, we use the bibliographic review as a work methodology, we search for authors from various disciplines, who suggest thinking about dying well, the subjective and chronological time. The review consists of an approach to the concepts, ideas, theories that motivate us to raise some questions regarding our practice, and thus, produce this writing. The following questions will guide this analysis: what happens when the chronological time of the disease is not the necessary time to accompany the speed with which death presents itself in the subjectivity of the patient and their family?, is there an ideal death?, should we all go through an ideal death?, what happens when chronological time does not allow us to subjectively elaborate the idea of dying?, can the loving and sympathetic care of the diseased body, by emphasizing the inherent dignity of the human being, have an impact in the perception of chronological time?.